Confinement Behavior - García-Castillo, Fernando; Ramos-Soler, Irene; García-del-Castillo, José A. (Journal of Psychology and Psychotherapy Research, 2021)
Some events are drivers for a change in the way we live life. When these events are not controllable, as has been the case with the coronavirus pandemic, everything is precipitated and the mechanisms of change are accelerated regardless of the type of culture, society, or economy in which they take place. Possibly it is the circumstances that directly affect the health of the population that are the most critical and are the ones that cause the greatest concern and change. This is the first time in history that we have had the opportunity to study lockdown behavior at a global level, analyzing how it affects citizens’ way of life. The most widespread restrictions in most countries of the world have revolved around increasing physical distance, lockdowns (total, by districts, or by specific areas), curfews (variable depending on the severity of the situation of each place), mandatory isolation in the case of testing positive for the infection, the suppression of all kinds of activities (cultural, sports, leisure), and the promotion of remote working to avoid, as much as possible, being in contact with others. The two main characteristics of mandatory isolation are, on the one hand, complete physical isolation from family and friends and, on the other, the absolute restriction of free movement. Both measures, also being combined with other factors, can generate significant changes in the levels of anxiety and stress of confined people. This is due to these people experiencing emotions of fear regarding illness and death, the possible loss of their jobs, the consequent economic problems, and the probability of increasing their level of being sedentary as a result of not being able to go outside to exercise. In this study, we propose, from a theoretical point of view, the precedents and consequences of lockdown behavior regarding the dimensions that we consider fundamental in people's lives. We analyze how lockdown influences lifestyle, from eating habits to sleeping patterns, digital behavior, physical activity, and emotional state, reaching the theoretical conclusion that all of these aspects can be significantly altered.